The 16-ka phytolith record of Lake Ngami, Botswana, and its assessment with records of pollen and lacustrine dynamics - Carlos Cordova; Louis Scott (Review of Palaeobotany and Palynology, 2026)

The potential role of wastewater surveillance signals for overdose prevention in Marin County, California, February 2023–June 2024 - Haylea Hannah; Sophie Zhu; Zerleen Quader; Souci Louis; Priyanka Thatipamala; Lee Ann Prebil; Megan Bias; Carly Adams; Heather E Reese; Jessica Ricaldi; Scott Santibañez; Jonathan Yoder; et al. (Water Research, 2026)

Palm, mangrove and Podocarpaceae environments along the southwestern African coast during the Paleogene–Neogene transition - Moteng E. Moseri; Frank H. Neumann; Nikiwe Z. Ndlovu; Eugene W. Bergh; Louis Scott; Mabrouk Bachari; Marion K. Bamford; Tshiamo T. O. Mmatladi; Thokozani Mahlangu (Palynology, 2026)

Salinity effects on dietary assimilation of eight trace elements and their distributions among body components in euryhaline diamond sturgeon - Ross A. Jeffree; Scott J. Markich; Francois Oberhaensli; Jean-Louis Teyssie (Marine Pollution Bulletin, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Small methane emissions from pasture observed with eddy covariance and flux-gradient methods: are they real or artefacts? - Johannes Laubach; Aaron M. Wall; John E. Hunt; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; Louis A. Schipper (Agricultural and Forest Meteorology, 2026)

Reinterpretation of palaeoecological records from Tswaing crater (South Africa) reveals the crucial role of fire in shaping savanna - Abraham Nqabutho Dabengwa; Louis Scott; Marion Bamford (Quaternary International, 2025)

Carbon dioxide removal during dissolution of granular basalt: A mass balance test of enhanced rock weathering at the hillslope scale - Charles J. Cunningham; Andrew Guertin; Marine Gelin; Louis A. Derry; Hannes H. Bauser; Minseok Kim; Jennifer L. Druhan; Scott Saleska; Peter A. Troch; Jon Chorover (Earth and Planetary Science Letters, 2025)

Morphology and ecological significance of Holocene palynomorphs from the Indian Ocean Coastal Belt Biome of South Africa - Angela Charles Effiom; Frank Harald Neumann; Louis Scott; Marion Kathleen Bamford (Palynology, 2025)

Ecological and allergenic significance of atmospheric pollen spectra from a Grassland-Savanna ecotone in North West province, South Africa - Frank Harald Neumann; Dorra Gharbi; Linus Ajikah; Louis Scott; Sarel Cilliers; Jurgens Staats; Dilys Berman; Moteng Elizabeth Moseri; Keneilwe Podile; Nikiwe Ndlovu; Tshiamo Mmatladi; Jonny Peter (Palynology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Biokinetics of Americium-241 in the euryhaline diamond sturgeon Acipenser gueldenstaedtii following its uptake from water or food - Ross A. Jeffree; Scott J. Markich; Francois Oberhaensli; Jean-Louis Teyssie (Journal of Environmental Radioactivity, 2024)

Effects of dairy farming management practices on carbon balances in New Zealand’s grazed grasslands: Synthesis from 68 site-years - Aaron M. Wall; Johannes Laubach; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; John E. Hunt; Paul L. Mudge; David Whitehead; Louis A. Schipper (Agriculture, Ecosystems & Environment, 2024)

Maternal transfer of trace elements to shark eggs and their dietary assimilation efficiencies - Ross A. Jeffree; Francois Oberhaensli; Jean-Louis Teyssie; Scott J. Markich (Marine Pollution Bulletin, 2024)

Methane emissions from animal agriculture: Micrometeorological solutions for challenging measurement situations - Johannes Laubach; Thomas K. Flesch; Christof Ammann; Mei Bai; Zhiling Gao; Lutz Merbold; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; John E. Hunt; Aaron M. Wall; Louis A. Schipper (Agricultural and Forest Meteorology, 2024)

Revealing the activity and selectivity of atomically dispersed Ni in Zn3In2S6 for benzyl alcohol photoreforming - Denny Gunawan; Li Yuan Lau; Jodie A. Yuwono; Priyank V. Kumar; Louis Oppong-Antwi; Inga Kuschnerus; Shery L.Y. Chang; Rosalie K. Hocking; Rose Amal; Jason Scott; Cui Ying Toe (Chemical Engineering Journal, 2024)

Geographical movements, site fidelity and connectivity of killer whales within and outside herring grounds in Icelandic coastal waters - Tatiana M. J. Marchon; Marianne H. Rasmussen; Charla J. Basran; Megan Whittaker; Chiara G. Bertulli; Cathy Harlow; Rob Lott; Oliver Boisseau; Frédéric Gendron; Luisa Guo; Tess Hudson; Hörður Jónsson; et al. (Marine Biology, 2024)

Cadmium-109 Internal Kinetics in Diamond Sturgeon Acipenser gueldenstaedtii are Strongly Influenced by Salinity, Exposure Pathway and History - Ross A. Jeffree; Scott J. Markich; Francois Oberhaensli; Jean-Louis Teyssie (Archives of Environmental Contamination and Toxicology, 2023)

Sugars and cuticular waxes impact sugarcane aphid (Melanaphis sacchari) colonization on different developmental stages of sorghum - Juan Betancurt Cardona; Sajjan Grover; Michael J. Bowman; Lucas Busta; Pritha Kundu; Kyle G. Koch; Gautam Sarath; Scott E. Sattler; Joe Louis (Plant Science, 2023)

Development and Evaluation of High-Density SNP Arrays for the Eastern Oyster Crassostrea virginica - Ximing Guo; Jonathan B. Puritz; Zhenwei Wang; Dina Proestou; Standish Allen; Jessica Small; Klara Verbyla; Honggang Zhao; Jaime Haggard; Noah Chriss; Dan Zeng; Kathryn Lundgren; et al. (Marine Biotechnology, 2023)

Sorghum cuticular waxes influence host plant selection by aphids - Juan Betancurt Cardona; Sajjan Grover; Lucas Busta; Scott E. Sattler; Joe Louis (Planta, 2023)

Interplay of phytohormones facilitate sorghum tolerance to aphids - Sajjan Grover; Earl Agpawa; Gautam Sarath; Scott E. Sattler; Joe Louis (Plant Molecular Biology, 2022)

Late Holocene environmental change and anthropogenic: Ecosystem interaction on the Laikipia Plateau, Kenya - Veronica Muiruri; Rob Marchant; Stephen M. Rucina; Louis Scott; Paul J. Lane (Ambio, 2022)
East African ecosystems have been shaped by long-term socio-ecological–environmental interactions. Although much previous work on human–environment interrelationships have emphasised the negative impacts of human interventions, a growing body of work shows that there have also often been strong beneficial connections between people and ecosystems, especially in savanna environments. However, limited information and understanding of past interactions between humans and ecosystems of periods longer than a century hampers effective management of contemporary environments. Here, we present a late Holocene study of pollen, fern spore, fungal spore, and charcoal analyses from radiocarbon-dated sediment sequences and assess this record against archaeological and historical data to describe socio-ecological changes on the Laikipia Plateau in Rift Valley Province, Kenya. The results suggest a landscape characterised by closed forests between 2268 years before present (cal year BP) and 1615 cal year BP when there was a significant change to a more open woodland/grassland mosaic that continues to prevail across the study area. Increased amounts of charcoal in the sediment are observed for this same period, becoming particularly common from around 900 cal year BP associated with fungal spores commonly linked to the presence of herbivores. It is likely these trends reflect changes in land use management as pastoral populations improved and extended pasture, using fire to eradicate disease-prone habitats. Implications for contemporary land use management are discussed in the light of these findings.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Novel Caulobacter bacteriophages illustrate the diversity of the podovirus genus Rauchvirus - Bert Ely; Jana Liese; Scott Corley; Doreen Nguyen; Kiesha Wilson; Louis Berrios (Archives of Virology, 2020)

Old growth Afrotropical forests critical for maintaining forest carbon - John R. Poulsen; Vincent P. Medjibe; Lee J. T. White; Zewei Miao; Ludovic Banak‐Ngok; Chris Beirne; Connie J. Clark; Aida Cuni‐Sanchez; Mathias Disney; Jean‐Louis Doucet; Michelle E. Lee; Simon L. Lewis; et al. (Global Ecology and Biogeography, 2020)
Aim Large trees [≥ 70 cm diameter at breast height (DBH)] contribute disproportionately to aboveground carbon stock (AGC) across the tropics but may be vulnerable to changing climate and human activities. Here we determine the distribution, drivers and threats to large trees and high carbon forest. Location Central Africa. Time period Current. Major taxa studied Trees. Methods Using Gabon's new National Resource Inventory of 104 field sites, AGC was calculated from 67,466 trees from 578 species and 97 genera. Power and Michaelis–Menten models assessed the contribution of large trees to AGC. Environmental and anthropogenic drivers of AGC, large trees, and stand variables were modelled using Akaike’s information criterion (AIC) weights to calculate average regression coefficients for all p ossible models. Results Mean AGC for trees ≥ 10 cm DBH in Gabonese forestlands was 141.7 Mg C/ha, with averages of 166.6, 171.3 and 96.6 Mg C/ha in old growth, concession and secondary forest. High carbon forests occurred where large trees are most abundant: 31% of AGC was stored in large trees (2.3% of all stems). Human activities largely drove variation in AGC and large trees, but climate and edaphic conditions also determined stand variables (basal area, tree height, wood density, stem density). AGC and large trees increased with distance from human settlements; AGC was 40% lower in secondary than primary and concession forests and 33% higher in protected than non‐managed areas. Main conclusions AGC and large trees were negatively associated with human activities, highlighting the importance of forest management. Redefining large trees as ≥ 50 cm DBH (4.3% more stems) would account for 20% more AGC. This study demonstrates that protecting relatively undisturbed forests can be disproportionately effective in conserving carbon and suggests that including sustainable forestry in programs like reduced emissions for deforestation and forest degradation could maintain carbon dense forests in logging concessions that are a large proportion of remaining Central African forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Acidification in the U.S. Southeast: Causes, Potential Consequences and the Role of the Southeast Ocean and Coastal Acidification Network - Emily R. Hall; Leslie Wickes; Louis E. Burnett; Geoffrey I. Scott; Debra Hernandez; Kimberly K. Yates; Leticia Barbero; Janet J. Reimer; Mohammed Baalousha; Jennifer Mintz; Wei-Jun Cai; J. Kevin Craig; et al. (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

In Memoriam: Fernando Lopes da Silva (1935–2019) - Christoph M. Michel; Sylvain Baillet; Christian Benar; Olivier Bertrand; Jean Gotman; Bin He; Geert-Jan Huiskamp; Louis Lemieux; Scott Makeig; Alvaro Pascual-Leone; Riitta Salmelin; Stefano Seri; et al. (Brain Topography, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Resistance to greenbugs in the sorghum nested association mapping population - Sajjan Grover; Braden Wojahn; Suresh Varsani; Scott E. Sattler; Joe Louis (Arthropod-Plant Interactions, 2019)

Comparing depth and seabed terrain preferences of individually identified female humpback whales ( Megaptera novaeangliae ), with and without calf, off Maui, Hawaii - Adam A. Pack; Louis M. Herman; Alison S. Craig; Scott S. Spitz; James O. Waterman; Elia Y. K. Herman; Mark H. Deakos; Siri Hakala; Carley Lowe (Marine Mammal Science, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

A practical guide for the identification of major sulcogyral structures of the human cortex - Christophe Destrieux; Louis Marie Terrier; Frédéric Andersson; Scott A. Love; Jean-Philippe Cottier; Henri Duvernoy; Stéphane Velut; Kevin Janot; Ilyess Zemmoura (Brain Structure and Function, 2017)

Irrigating grazed pasture decreases soil carbon and nitrogen stocks - Paul L. Mudge; Francis M. Kelliher; Trevor L. Knight; Denis O'Connell; Scott Fraser; Louis A. Schipper (Global Change Biology, 2017)
The sustainability of using irrigation to produce food depends not only on the availability of sufficient water, but also on the soil's ‘response’ to irrigation. Stocks of carbon (C) and nitrogen (N) are key components of soil organic matter ( SOM ), which is important for sustainable agricultural production. While there is some information about the effects of irrigation on soil C stocks in cropping systems, there is a paucity of such studies in pastoral food production systems. For this study, we sampled soils from 34 paired, irrigated and unirrigated pasture sites across New Zealand ( NZ ) and analysed these for total C and N. On average, irrigated pastures had significantly ( P 0.05) less soil carbon (C) and nitrogen (N) than adjacent unirrigated pastures, with differences of 6.99 t C ha −1 and 0.58 t N ha −1 in the uppermost 0.3 m. Differences in C and N tended to occur throughout the soil profile, so the cumulative differences increased with depth, and the proportion of the soil C lost from deeper horizons was large. There were no relationships between differences in soil C and N stocks and the length of time under irrigation. This study suggests SOM will decrease when pastures under a temperate climate are irrigated. On this basis, increasing the area of temperate pasture land under irrigation would result in more CO 2 in the atmosphere and may directly and indirectly increase N leaching to groundwater. Given the large and increasing area of land being irrigated both in NZ and on a global scale, there is an urgent need to determine whether the results found in this study are also applicable in other regions and under different land management systems (e.g. arable).

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Projected Tree Species Redistribution Under Climate Change: Implications for Ecosystem Vulnerability Across Protected Areas in the Eastern United States - Scott G. Zolkos; Patrick Jantz; Tina Cormier; Louis R. Iverson; Daniel W. McKenney; Scott J. Goetz (Ecosystems, 2015)

18,000 years of grassland evolution in the summer rainfall region of South Africa: evidence from Mahwaqa Mountain, KwaZulu-Natal - Frank H. Neumann; Gregory A. Botha; Louis Scott (Vegetation History and Archaeobotany, 2014)

An assessment of endocrine activity in Australian rivers using chemical and in vitro analyses - Philip D. Scott; Michael Bartkow; Stephen J. Blockwell; Heather M. Coleman; Stuart J. Khan; Richard Lim; James A. McDonald; Helen Nice; Dayanthi Nugegoda; Vincent Pettigrove; Louis A. Tremblay; Michael St. J. Warne; et al. (Environmental Science and Pollution Research, 2014)

Hypothesis-independent pathway analysis implicates GABA and Acetyl-CoA metabolism in primary open-angle glaucoma and normal-pressure glaucoma - Jessica N. Cooke Bailey; Brian L. Yaspan; Louis R. Pasquale; Michael A. Hauser; Jae H. Kang; Stephanie J. Loomis; Murray Brilliant; Donald L. Budenz; William G. Christen; John Fingert; Douglas Gaasterland; Terry Gaasterland; et al. (Human Genetics, 2014)

Neutral and selective processes shape MHC gene diversity and expression in stocked brook charr populations ( S alvelinus fontinalis ) - Fabien C. Lamaze; Scott A. Pavey; Eric Normandeau; Gabriel Roy; Dany Garant; Louis Bernatchez (Molecular Ecology, 2014)
The capacity of an individual to battle infection is an important fitness determinant in wild vertebrate populations. The major histocompatibility complex ( MHC ) genes are crucial for a host's adaptive immune system to detect pathogens. However, anthropogenic activities may disrupt natural cycles of co‐evolution between hosts and pathogens. In this study, we investigated the dynamic sequence and expression variation of host parasite interactions in brook charr ( S alvelinus fontinalis ) in a context of past human disturbance via population supplementation from domestic individuals. To do so, we developed a new method to examine selection shaping MHC diversity within and between populations and found a complex interplay between neutral and selective processes that varied between lakes that were investigated. We provided evidence for a lower introgression rate of domestic alleles and found that parasite infection increased with domestic genomic background of individuals. We also documented an association between individual MHC alleles and parasite taxa. Finally, longer cis ‐regulatory minisatellites were positively correlated with MHC II down‐regulation and domestic admixture, suggesting that inadvertent selection during domestication resulted in a lower immune response capacity, through a trade‐off between growth and immunity, which explained the negative selection of domestic alleles at least under certain circumstances.

Genome-wide association study and meta-analysis of intraocular pressure - A. Bilge Ozel; Sayoko E. Moroi; David M. Reed; Melisa Nika; Caroline M. Schmidt; Sara Akbari; Kathleen Scott; Frank Rozsa; Hemant Pawar; David C. Musch; Paul R. Lichter; Doug Gaasterland; et al. (Human Genetics, 2014)

Humpback whale song: who sings? - Louis M. Herman; Adam A. Pack; Scott S. Spitz; Elia Y. K. Herman; Kathryn Rose; Siri Hakala; Mark H. Deakos (Behavioral Ecology and Sociobiology, 2013)

Nonparallelism in MHCII β diversity accompanies nonparallelism in pathogen infection of lake whitefish ( C oregonus clupeaformis ) species pairs as revealed by next‐generation sequencing - Scott A. Pavey; Maelle Sevellec; William Adam; Eric Normandeau; Fabien C. Lamaze; Pierre‐Alexandre Gagnaire; Marie Filteau; Francois Olivier Hebert; Halim Maaroufi; Louis Bernatchez (Molecular Ecology, 2013)
Major histocompatibility ( MHC ) immune system genes may evolve in response to pathogens in the environment. Because they also may affect mate choice, they are candidates for having great importance in ecological speciation. Here, we use next‐generation sequencing to test the general hypothesis of parallelism in patterns of MHCII β diversity and bacterial infections among five dwarf and normal whitefish sympatric pairs. A second objective was to assess the functional relationships between specific MHCII β alleles and pathogens in natural conditions. Each individual had between one and four alleles, indicating two paralogous loci. In C liff Lake, the dwarf ecotype was monomorphic for the most common allele. In W ebster Lake, the skew in the allelic distribution was towards the same allele but in the normal ecotype, underscoring the nonparallel divergence among lakes. Our signal of balancing selection matched putative peptide binding region residues in some cases, but not in others, supporting other recent findings of substantial functional differences in fish MHCII β compared with mammals. Individuals with fewer alleles were less likely to be infected; thus, we found no evidence for the heterozygote advantage hypothesis. MHCII β alleles and pathogenic bacteria formed distinct clusters in multivariate analyses, and clusters of certain alleles were associated with clusters of pathogens, or sometimes the absence of pathogens, indicating functional relationships at the individual level. Given that patterns of MHCII β and bacteria were nonparallel among dwarf and normal whitefish pairs, we conclude that pathogens driving MHCII β evolution did not play a direct role in their parallel phenotypic evolution.

Mapping phenotypic, expression and transmission ratio distortion QTL using RAD markers in the Lake Whitefish (Coregonus clupeaformis) - Pierre‐Alexandre Gagnaire; Eric Normandeau; Scott A. Pavey; Louis Bernatchez (Molecular Ecology, 2013)
The evolution of reproductive isolation in an ecological context may involve multiple facets of species divergence on which divergent selection may operate. These include variation in quantitative phenotypic traits, regulation of gene expression, and differential transmission of particular allelic combinations. Thus, an integrative approach to the speciation process involves identifying the genetic basis of these traits, in order to understand how they are affected by divergent selection in nature and how they ultimately contribute to reproductive isolation. In the Lake Whitefish ( Coregonus clupeaformis ), dwarf and normal species pairs sympatrically occur in several North American postglacial lakes. The limnetic dwarf whitefish distinguishes from its normal benthic relative by numerous life history, behavioural, morphological and gene expression traits, in relation with the exploitation of distinct ecological niches. Here, we have applied the RAD‐Sequencing method to a hybrid backcross family to reconstruct a high‐density genetic linkage map and perform QTL mapping in the Lake Whitefish. The 3061 cM map encompassed 3438 segregating RAD markers distributed over 40 linkage groups, for an average resolution of 0.89 cM. We mapped phenotypic and expression QTL underlying ecologically important traits as well as transmission ratio distortion QTL, and identified genomic regions harbouring clusters of such QTL. A narrow genomic region strongly associated with sex determination was also evidenced. Positional and functional information revealed in this study will be useful in ongoing population genomic studies to illuminate our understanding of the genomic architecture of reproductive isolation between whitefish species pairs.

Full length MHC IIβ exon 2 primers for salmonids: a new resource for next generation sequencing - Scott A. Pavey; Fabien C. Lamaze; Dany Garant; Louis Bernatchez (Conservation Genetics Resources, 2011)

Long‐term survival of humpback whales radio‐tagged in Alaska from 1976 through 1978 - Sally A. Mizroch; Michael F. Tillman; Susan Jurasz; Janice M. Straley; Olga Von Ziegesar; Louis M. Herman; Adam A. Pack; Scott Baker; Jim Darling; Debbie Glockner‐Ferrari; Mark Ferrari; Dan R. Salden; et al. (Marine Mammal Science, 2011)
Invasive tags designed to provide information on animal movements through radio or satellite monitoring have tremendous potential for the study of whales and other cetaceans. However, to date there have been no published studies on the survival of tagged animals over periods of years or decades. Researchers from the National Marine Mammal Laboratory and the Woods Hole Oceanographic Institution tracked five humpback whales with implanted radio tags in southeastern Alaska in August 1976 and July 1977, and tracked two humpback whales in Prince William Sound, Alaska, in June 1978. All seven of these individually identified humpback whales were resighted at least 20 yr after first being tagged, and five of the seven have been observed for more than 30 yr; some of them are among the most resighted humpback whales in the North Pacific. Photos of tagging sites taken during and subsequent to tagging operations show persistent but superficial scarring and no indication of infection. These pioneering field studies demonstrated both long‐term survival of the whales and the short‐term effects of deploying radio tags, which at the time were larger and more invasive than those typically used today.

NeuroAIDS in Africa - Kevin Robertson; Jeff Liner; James Hakim; Jean-Louis Sankalé; Igor Grant; Scott Letendre; David Clifford; Amadou Gallo Diop; Assan Jaye; Georgette Kanmogne; Alfred Njamnshi; T. Dianne Langford; et al. (Journal of NeuroVirology, 2010)

Scavenging and retention of bismuth by marine plankton and biogenic particles - Scott W. Fowler; Jean-Louis Teyssie; Thomas M. Church (Limnology and Oceanography, 2010)
We did radiotracer experiments using 207 Bi to quantify the bioavailability, accumulation, and retention of bismuth in marine plankton and biogenic detritus. The accumulation of 207 Bi by two species of phytoplankton ( Dunaliella tertiolecta and Emiliana huxleyi ) was very rapid, approaching steady state after ~1 d. Emiliana cells without coccoliths reached a volume concentration factor (VCF) roughly twice that attained by cells with coccoliths. VCFs were 5 × 10 5 for Dunaliella and (4–9) × 10 6 for Emiliana after exposure for approximately 5 d. The radioactivity associated with Dunaliella was released with a biological half‐time of 3–5 d. Copepods ( Anomalocera patersoni and Acartia species) grazing radiolabeled Dunaliella assimilated ~4% of the ingested 207 Bi. Unassimilated radioactivity, voided in fecal pellets, was lost from pellets relatively slowly (half‐times of 26 d for Anomalocera and 58 d for Acartia ). These release rates were similar to copepod fecal pellets that had scavenged 207 Bi directly from water. Scavenging of bismuth from water by fecal pellets was considerable and extremely rapid, and uptake rates were similar to those of various size fractions of marine snow collected in a sediment trap. Release of scavenged 207 Bi from the fresh fecal pellets was relatively slow, and very little release of radionuclide from the different size fractions of marine snow was observed. The biogeochemical behavior of bismuth in the marine environment closely resembles that of other particle‐reactive uranium‐thorium (U–Th) series and transuranic elements.

Ten Putative Contributors to the Obesity Epidemic - Emily J. McAllister; Nikhil V. Dhurandhar; Scott W. Keith; Louis J. Aronne; Jamie Barger; Monica Baskin; Ruth M. Benca; Joseph Biggio; Mary M. Boggiano; Joe C. Eisenmann; Mai Elobeid; Kevin R. Fontaine; et al. (Critical Reviews in Food Science and Nutrition, 2009)

Direct effects of soybean varietal selection and Aphis glycines-resistant soybeans on natural enemies - Jonathan G. Lundgren; Louis S. Hesler; Kelley Tilmon; Kenton Dashiell; Roy Scott (Arthropod-Plant Interactions, 2009)

Landscape genetic analyses reveal cryptic population structure and putative selection gradients in a large‐scale estuarine environment - R. J. SCOTT McCAIRNS; LOUIS BERNATCHEZ (Molecular Ecology, 2008)
Disentangling the relative contributions of selective and neutral processes underlying phenotypic and genetic variation under natural, environmental conditions remains a central challenge in evolutionary ecology. However, much of the variation that could be informative in this area of research is likely to be cryptic in nature; thus, the identification of wild populations suitable for study may be problematic. We use a landscape genetics approach to identify such populations of three‐spined stickleback inhabiting the Saint Lawrence River estuary. We sampled 1865 adult fish over multiple years. Individuals were genotyped for nine microsatellite loci, and georeferenced multilocus data were used to infer population groupings, as well as locations of genetic discontinuities, under a Bayesian model framework ( geneland ). We modelled environmental data using nonparametric multiple regression to explain genetic differentiation as a function of spatio‐ecological effects. Additionally, we used genotype data to estimate dispersal and gene flow to parameterize a simple model predicting adaptive vs. plastic divergence between demes. We demonstrate a bipartite division of the genetic landscape into freshwater and maritime zones, independent of geographical distance. Moreover, we show that the greatest proportion of genetic variation (31.5%) is explained by environmental differences. However, the potential for either adaptive or plastic divergence between demes is highly dependent upon the strength of migration and selection. Consequently, we highlight the utility of landscape genetics as a tool for hypothesis generation and experimental design, to identify focal populations and putative selection gradients, in order to distinguish between phenotypic plasticity and local adaptation.

Glider observations of sediment resuspension in a Middle Atlantic Bight fall transition storm - Scott Glenn; Clayton Jones; Michael Twardowski; Louis Bowers; John Kerfoot; Josh Kohut; Doug Webb; Oscar Schofield (Limnology and Oceanography, 2008)
In October of 2003 a fleet of autonomous underwater gliders began a time series of transects across the New Jersey shelf. The gliders are equipped with a conductivity‐temperature‐depth sensor, and some carry optical ECO‐sensor pucks. The physical‐optical data are used to examine storm‐induced sediment resuspension. There are two types of storm response found. In summer, the seasonal stratification limits midshelf sediment resuspension to below the pycnocline even during hurricanes. In contrast, winter storms suspend sediment throughout the full water column. The transition between summer and winter seasons starts with surface cooling that preconditions the shelf for rapid mixing during fall storms. The mixing storm of October 2003 was a classic northeaster. Early in the storm when waves were high, sediment resuspension was limited to below the pycnocline. After the pycnocline eroded through growth of the bottom boundary layer, particles immediately filled the full water column. The spectral ratio of backscatter indicated that the particles were likely similar materials both before and after the stratification was eroded. The backscatter profiles in the bottom boundary layer decay with distance from the bed at rates consistent with theory but with variable slopes. The reduced slope of the backscatter profiles increased after stratification was lost, which is consistent with an increase in vertical transport or turbulent mixing. Wave bottom orbital velocities during this time were decreasing, and the glider vertical velocities showed no enhancement consistent with Langmuir cells. Enhanced mixing was related to the interaction of the surface and bottom boundary layers while the stratification was eroded, and the observed variability in the resuspension during the event was also due to the tide.

Interactions and competition within the microbial community of the human colon: links between diet and health - Harry J. Flint; Sylvia H. Duncan; Karen P. Scott; Petra Louis (Environmental Microbiology, 2007)
Summary The microbiota of the human intestinal tract play an important role in health, in particular by mediating many of the effects of diet upon gut health. Surveys of 16S rRNA sequence diversity in the human colon have emphasized the low proportion of sequences that match cultured bacterial species. This may reflect limited recent effort on cultivation rather than inherent unculturability, however, as anaerobic isolation methods can apparently recover a wide range of the diversity found. A combination of information from representative cultures, molecular tools for enumeration and tracking of bacterial metabolites offers the most powerful route to understanding the roles played by different groups of bacteria in the gut ecosystem. Progress is being made for example in defining key functional groups including primary colonizers of insoluble dietary substrates, and major contributors to metabolites such as butyrate that influence the health of the gut mucosa. There is increasing evidence that bacterial populations in the large intestine respond to changes in diet, in particular to the type and quantity of dietary carbohydrate. A general consequence of increased carbohydrate consumption is to reduce the pH of the gut lumen, which is likely to play a major role in determining bacterial metabolism and competition. Oligosaccharides used as dietary prebiotics must inevitably have complex effects upon the bacterial community that include non‐target organisms and the consequences of metabolic cross‐feeding and changes in the gut environment.

Sulphate, Nitrogen and Base Cation Budgets at 21 Forested Catchments in Canada, the United States and Europe - Shaun A. Watmough; Julian Aherne; Christine Alewell; Paul Arp; Scott Bailey; Tom Clair; Peter Dillon; Louis Duchesne; Catherine Eimers; Ivan Fernandez; Neil Foster; Thorjorn Larssen; et al. (Environmental Monitoring and Assessment, 2005)

Fossil hyrax dung and evidence of Late Pleistocene and Holocene vegetation types in the Namib Desert - Louis Scott; Eugene Marais; George A. Brook (Journal of Quaternary Science, 2004)
Pollen was derived from fossil dung of herbivorous hyraxes, deposited in a rock shelter on the highest mountain in Namibia, Dâures or Brandberg, situated on the Namib Desert margin. Radiocarbon dating ranging in age between modern times and 30 000 yr BP showed it represents the first empirical pollen evidence of continental palaeovegetation during the Late Pleistocene along the western escarpment of southern Africa. The initial results indicate Last Glacial Maximum vegetation differed totally from the current pattern as vegetation types were dominated by small Asteraceae shrubs, in contrast to those of the Holocene and modern times which show more succulents, grass and woody elements (arboreal pollen). The results suggest that Cape floral communities did not reach into the tropics along the western escarpment of Africa, despite such pollen types occurring in marine cores. Copyright © 2004 John Wiley & Sons, Ltd.

The Expanding Role of Ocean Color and Optics in the Changing Field of Operational Oceanography - Scott Glenn; Oscar Schofield; Tommy Dickey; Robert Chant; Josh Kohut; Hervé Barrier; Jennifer Bosch; Louis Bowers; Elizabeth Creed; Chip Haldeman; Eli Hunter; John Kerfoot; et al. (Oceanography, 2004)

Pollen analysis of Iron Age cow dung in southern Africa - Jos S. Carrin; Louis Scott; Tom Huffman; Cobus Dreyer (Vegetation History and Archaeobotany, 2000)

MEASURING SIZES OF HUMPBACK WHALES ( MEGAPTERA NOVAEANGLIAE ) BY UNDERWATER VIDEOGRAMMETRY - Scott S. Spitz; Louis M. Herman; Adam A. Pack (Marine Mammal Science, 2000)

Twentieth century changes in montane vegetation in the eastern Free State, South Africa, derived from palynology of hyrax dung middens - Jose S. Carrión; Louis Scott; John C. Vogel (Journal of Quaternary Science, 1999)

Biome reconstruction from pollen and plant macrofossil data for Africa and the Arabian peninsula at 0 and 6000 years - Dominique Jolly; I. Colin Prentice; Raymonde Bonnefille; Aziz Ballouche; Martin Bengo; Patrice Brenac; Guillaume Buchet; David Burney; Jean‐Pierre Cazet; Rachid Cheddadi; Therese Edorh; Hilaire Elenga; et al. (Journal of Biogeography, 1998)
Biome reconstruction from pollen and plant macrofossil data provides an objective method to reconstruct past vegetation. Biomes for Africa and the Arabian peninsula have been mapped for 6000 years bp and provide a new standard for the evaluation of simulated palaeovegetation distributions. A test using modern pollen data shows the robustness of the biomization method, which is able to predict the major vegetation types with a high confidence level. The application of the procedure to the 6000 years data set (pollen and plant macrofossil analyses) shows systematic differences from the present that are consistent with the numerous previous regional and continental interpretations, while providing a more extensive and more objective basis for such interpretations. Madagascar, eastern, southern and central Africa show only minor changes in terms of biomes, compared to present. Major changes in biome distributions occur north of 15°N, with steppe in many low‐elevation sites that are now desert, and temperate xerophytic woods/scrub and warm mixed forest in the Saharan mountains. These shifts in biome distributions imply significant changes in climate, especially precipitation, between 6000 years and present, reflecting a change in monsoon extent combined with a southward expansion of Mediterranean influence.

Landscape Modeling for Everglades Ecosystem Restoration - Donald L. DeAngelis; Louis J. Gross; Michael A. Huston; Wilfried F. Wolff; D. Martin Fleming; E. Jane Comiskey; Scott M. Sylvester (Ecosystems, 1998)